Visualization of robust two-dimensional bulk states with suppressed surface state on epitaxial PdCoO₂ thin films with bipolar surfaces - Kawamoto, Tomoki (2023)
Epitaxial thin films of metallic delafossites are a recent topic of intense investigation due to their intriguing electronic states. Using in situ angle-resolved photoemission spectroscopy, we investigated the electronic states of epitaxial PdCoO2 thin films with high crystalline quality and bipolar surface with mixed termination. On this characteristic surface, we observed a surprisingly prominent bulklike single hexagonal large Fermi surface with suppressed surface state. Firstly, observation of a sharp Fermi surface relies on the minimized atomic scale disorder in our high-quality film surface. Additionally, the predominantly two-dimensional bulk electronic state with the Fermi group velocity parallel to the plane of PdCoO2 is expected to make the near-surface bulklike state less sensitive to the scattering by longer length scale random bipolar surface potentials. Furthermore, the origin of the suppressed surface state can be interpreted by screening of the polarity on the surface, which is qualitatively supported by density functional theory calculation. These findings are invaluable for accelerating the search for exotic functionalities in epitaxial ultrathin films and heterostructures of metallic delafossites.